Birmingham Royal Orthopedic Hospital (BROH) CAM Offset: A Simplified Metric for Detection of CAM Morphology of the Hip - Sai Niharika Gavvala; Kapil Shirodkar; Mohsin Hussein; Nathan Jenko; Karthikeyan P. Iyengar; Rajesh Botchu (Indian Journal of Radiology and Imaging)
Background CAM morphology of the hip is a disorder of abnormal morphology of the femoral head–neck junction associated with loss of the osseous sphericity of the femoral head. Several radiological measurements exist to detect CAM morphology of the hip.